HUBUNGAN STATUS GIZI DAN AKTIVITAS FISIK DENGAN KEBUGARAN JASMANI REMAJA - Ihda Nur Kasyifa; Mohammad Zen Rahfiludin; Suroto Suroto (UNUSA Press, 2018)
Physical fitness is one of the most important things especially for teens due to their highactivities. Factors that affect physical fitness such as physical activity and BMI/Age. This study aimsto find out the relationship between body mass index based on age (BMI/Age) and physical activitywith physical fitness of SMKN Jawa Tengah Semarang students. This study use quantitative approachwith cross sectional research method. Population used in this study are 118 tenth graders and thesampel are 55 students. Statistic analysis in this study use Kolmogorov-Smirnov and Rank Spearmantest. The result shows that most of 16-year-olds participants are 39 students (70,9%) and 45 studentsare male. Fourty nine students (81,8%) have normal BMI/Age which 28 participants have kind ofheavy activities and the physical fitness of 31 participants count as good categoy. This study showthere is no relationship between IMT/U with physical fitness (p = 0,252 and r = 0,160) and there isa relationship between physical activity with physical fitness (p = 0,003 and r = 0,391).